Dream images : a call to mental arms - Gackenbach, Jayne; Sheikh, A.A. (My University, 1991)
This new text is a state-of-the-art collection of essays representing varying points of view about dreams and the major research conducted in dream therapy today. Renewed interest into serious dream investigation in recent years has supplied a variety of conceptual and research applications into dream study. At long last, "Dream Images: A Call to Mental Arms", brings these current works together, in one complete, comprehensive volume.
Keywords: Dreams; Imagery (Psychology)